Global Diversity Character Development for Students through Economic Learning - Ninik Indawati (Aksara: Jurnal Ilmu Pendidikan Nonformal, 2022)
Associated with patterns of habituation, teachers can cultivate character through learning ethics, manners, and pronouncing words that are appropriate to the local context. One of the school's strategies can also get students used to saying the word "Good Morning" as an implementation of the 3S (smile, greeting, and greeting) policy at school. The attitude of students also did not go unnoticed. The teacher instills in students respect for elders, respect for teachers, for friends, a sense of belonging, including the habit of helping each other. For the purpose of assimilation, students from various religions are combined into study groups, so that awareness arises that they are Indonesians with one homeland and one bloodshed.